Risk of Developing Polycystic Ovarian Syndrome- Adolescent Girls - jit,, Satya (International Journal of Innovative Research in Medical Science, 2017)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrine disorders in women of fertile age, affecting 5-10% of the female population. Polycystic ovarian syndrome endocrine disturbance-affecting women during their reproductive years .The prevalence has been increasing in the adolescent population. In more than 40% of cases, PCOS is associated with obesity as well as impaired glucose tolerance, type 2 diabetes and the metabolic syndrome. In adult female patient, it is associated with an increased risk of endometrial cancer and is the most common identifiable cause of female infertility. While the pathophysiology of PCOS remains unclear, insulin resistance has been implicated as a major causative factor. In addition to this, several genes have been associated with this syndrome.1 Objective: To find out adolescent girls at risk of developing polycystic ovarian syndrome. Methodology: A Non-experimental descriptive research design was adopted to find out adolescent girls at risk of developing polycystic ovarian disorder in selected school. Purposive sampling technique was used. The data was collected on the sample of 100 adolescent girls in month of May 2013. A self-structured questionnaire and rating scale was used to find out adolescent girls at risk. The data was gathered and analysed by using statistical technique such as mean, mean percentage, standard deviation and chi-square value. Result: The study revealed that majority of girls i.e. 82% of girls to age group 13-15years and 12% at age 10-12year. Majority of girls i.e. 92% had normal menstrual cycle. Majority of girls i.e. 77% had mild hirsutism. Majority of girls’ i.e 50% had underweight. Majority of girls i.e. 65% had low waist hip ratio. Majority of girls’ i.e 86 % had normal blood pressure. Majority of girls i.e. 73% of adolescent girls without oligomenorrhea. Conclusion: Out of 100 adolescent girls, 5% of girls are at risk of developing polycystic ovarian syndrome. 8% of girls were having high weight hip ratio and 1% of adolescent girls were overweight. These girls were having a risk of developing polycystic ovarian syndrome and there is no relation between oligomenorrhea and hirsutism.